Relationship between nurses’ perception of ethical climates and job satisfaction in Jimma University Specialized Hospital, Oromia region, south west Ethiopia - Muktar Abadiga; Gugsa Nemera; Endalew Hailu; Getu Mosisa (BMC Nursing, 2019)
Abstract Background The ethical climate is one aspect of an organization which refers to the shared perceptions of ethically correct behaviors and way of handling ethically deviated behaviors. Increased awareness of the complexity of ethical issues in the health care setting has fueled interest in nursing ethics. However; there is limited information on the relationship between nurses’ perception of ethical climate and job satisfaction globally and no study was done on this issue particularly in Ethiopia. Therefore, this study was aimed to assess the relationship between nurses’ perception of ethical climates and job satisfaction in Jimma University Specialized Hospital, southwest Ethiopia, 2016. Methods Institutional based cross-sectional study was conducted on 266 nurses in Jimma University Specialized Hospital from March to April 2016. The study participants were invited by using simple random sampling method. Data were collected using self-administered questionnaires and were entered into Epidata 3.1 and analyzed using SPSS Version 20.0. Pearson’s correlation was used to assess the correlation between each dimension of the hospital ethical climate and job satisfaction of nurses. Variables significant at bivariate analysis (P < 0.25) were considered as a candidate for the multivariable linear regression analysis. All analyses were conducted at the 0.05 significance level. Results The percentage mean score for ethical climate and job satisfaction were 53.4 and 51.3% respectively. Law and code climate significantly influenced job satisfaction (β = 1.53, p = 0.000). Caring climate also significantly influenced nurses job satisfaction (β = 0.99, p = 0.000). The result also showed that an independence climate significantly influenced job satisfaction (β = 0.62, p = 0.041). On the other hand, rule climate and instrumental climate did not significantly affect job satisfaction (β = 0.380, p = 0.409 and β = − 0.208, p = 0.290 respectively). The adjusted R square was 0.601, indicating that 60.1% of the variations in job satisfactions was explained by ethical climate variables. Conclusion The different dimensions of ethical climates have a negative or positive impact on nurses’ job satisfaction and maintaining a positive ethical climate is key to increasing nurses’ job satisfaction.